Distribusi Dan Kelimpahan Bulu Babi (Echinoidea) Di Perairan Pulau Pasir Putih, Desa Sumberkima, Buleleng, Bali - Noviana, Ni Putu Emie; Julyantoro, Pande Gde Sasmita; Pebriani, Dewa Ayu Angga (Current Trends in Aquatic Science, 2019)
This research was conducted in the waters of Pasir Putih Island, Sumberkima Village, Gerokgak District, Buleleng Regency, Bali Province. This research was conducted from February to April 2018. This study aims to determine the distribution patterns and abundance of sea urchins, as well as water quality conditions in the waters of Pulau Pasir Putih. The method used was the method of observation and descriptive method. In this study, there were 5 species of sea urchins from 4 families, Echinothrix calamaris and Diadema setosum from Diadematidae family, Tripneustes gratilla from Toxopneustidae family, Brissus latecarinatus from Brissidae family and Echinometra mathaei from Echinometridae family. Echinothrix calamaris has uniform distribution pattern with Id <1, Diadema setosum has clustered distribution pattern with Id> 1, Tripneustes gratilla has clustered distribution pattern with Id> 1, Brissus latecarinatus has clustered distribution pattern with Id> 1, Echinometra mathaei has clustered distribution pattern with Id> 1. Echinothrix calamaris abundance is 2,42 ind/m 2 with relative abundance is 21%, Diadema setosum abundance is 6 ind/m 2 with relative abundance is 53%, Tripneustes gratilla abundance is 2,33 ind/m 2 with relative abundance is 3%, Brissus latecarinatus abundance is 0,17 ind/m 2 with relative abundance is 2%, and Echinometra mathaei abundance is 2,42 ind/m 2 with relative abundance is 21%. The value of community structure of sea urchins in the water of Pasir Putih Island indicates that medium diversity, unstable uniformity and low dominance. The condition of water quality in Pulau Pasir Putih was still within the threshold for the life of sea urchins. Based on the research, Diadema setosum species has the highest abundance with clustered pattern distribution.